Aviation pollution, tourism, and economic development: A study of the EKC hypothesis at regional level - Ngo T; Tsui WHK; Nguyen H (Institute of Economics of the Ural Branch of the Russian Academy of Sciences, 2024)
This study aimed to revisit the relationship between aviation pollution, tourism, and economic development i.e., the Environmental Kuznets Curve (EKC), particularly at the regional level, using New Zealand as a case study. Our study is the first to estimate the aviation pollution at regional airports (in New Zealand) and use them as proxy for the regional pollution in an EKC setting. We found evidence that the EKC exists at the regional level, where tourism and economic development helps improve the regional environment in the long run. It suggests that the environment policy should be tailored at regional rather than just at the national level. It also proposes a new approach for EKC studies at the regional level via the new pollution estimation. Among others, we found that the sustainable tourism policy has, and will, work well in New Zealand.
Keywords: Aviation; CO2 emissions; Economic development; Environmental Kuznets curve (EKC); New Zealand regions; Tourism